Social network size, personality and well-being in preretirement and retirement - Jurkuvėnas, Vytautas; Zamalijeva, Olga; Pakalniškienė, Vilmantė; Kairys, Antanas; Bagdonas, Albinas (Psichologija, 2017)
Focus on the well-being of retired adults, as well as people approaching retirement, has been growing in the psychological domain. Although well-being is an import aspect of life in any age, adults in preretirement and retirement face unique challenges. The impact of retirement on a person’s well-being may vary depending on many factors. The general aim of this study was to investigate the links that well-being has with social network size and personality in preretirement and retirement. Overall, 788 adults participated in this study. Participants were divided into two groups: younger than statutory retirement age (N = 368, M age = 55.56, SD = 3.68) and older than statutory retirement age (N = 420, M age = 72.25, SD = 7.42) individuals. The sample represents the composition of Lithuanian population over 50 years old. Participants completed a questionnaire including questions about their gender, age, education, retirement, social network size (Social network size questionnaire), personality (NEO five-factor inventory (NEO-FFI)) and well-being (The Lithuanian Well-Being Scale for adults (LPGS-S)). Results show that being fully retired and with neuroticism negatively relates to well-being. On the other hand, higher level of education, not being fully retired from work, extraversion, openness to experiences, agreeableness, conscientiousness and social network size positively relates to well-being. Personality traits that were most predictive of well-being were those that compared to demographic factors and social network size. Furthermore, for preretired individuals, the relationship between social network size and well-being was nonsignificant. In contrast, although small but significant differences were observed in the fully-retired, older adults group. Overall, the findings of this study show the importance of personality traits, social network size and retirement from work in older age.
Keywords: Social network size; personality traits; well-being; retirement